Performance Evaluation of Wireless Standards 802.11g and 802.11b on HTTP Application over AODV Protocol using OPNET - Qasim, Araz Jameel (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: Mobile ad hoc network (MANET) is a wireless network that does not contain an infrastructure. Nodes in this network are mobile and can join or leave out from the network in time. This feature can be used in many applications like collecting data. In addition to this mobile devices associated with stations are subject to change and continuity, which has led to many changes in the network topology. However, the problem with this network is that it is easily penetrated by hackers trying to break in, and therefore it should increase its efficiency using routing protocols. It is used to find the path between stations or update existing ones. Routing protocols are classified, as a proactive protocols (e.g., OLSR), reactive protocols (e.g., AODV and DSR), and hybrid protocol (e.g., TORA). The IEEE 802.11 wireless LAN, also known as Wi-Fi, has been classified into several standards including 802.11a, 802.11b and 802.11g. In this thesis, we used HTTP application to compare between IEEE 802.11b and 802.11g with different data rates. The routing protocol is used ad hoc on demand distance vector (AODV) protocol in this simulation. Performance of these routing protocols is analyzedby metrics; number of hops per route, HTTP page response time, HTTP object response time, route discovery time, media access delay, retransmission attempts(packet) and throughput.OPNET Modeler version 17.1 is used for modeling and simulatingad hoc network. It is demonstrated from the simulation results that; the media access delay of 802.11b with 11Mbps is greater than 802.11g in all used network cases of clients number. Average retransmission attempts of 802.11g is decreased by increasing the data rates (11Mbps, 24Mbps, and 54Mbps) of network, additionally, the peak value of retransmission attempts is where 24 clients are communicating with server for both standards 802.11b and 802.11g. Throughput of the network for 802.11g is greater than 802.11b for 11Mbps data rate. Additionally, throughput of both standards are increased by increasing the number of nodes that are communicating with the server. Keyword: MANET, AODV, HTTP, IEEE 802.11, OPNET. ………………………………………………………………………………………………………………………… ÖZ: Mobil özel amaca yönelik (ad hoc) ağ (MANET) altyapısı olmayan kablosuz bir ağdır. Bu ağdaki düğümler mobil olup zaman içerisinde ağa katılıp ağdan ayrılabilirler. Bu özellik veri toplama gibi birçok uygulamada kullanabilirler. Mobil cihazların hareketliliğinden dolayı zaman içerisinde ağın topolojisinde de değişikliler olmaktadır. Bu ağlardaki başlıca problem ağı yıkmak için dış saldırılara açık olması ve verimliliği artırmak için etkili yönlendirme protokollerine gerek duyulmasıdır. Yönlendirme protokolleri, istasyonlar arasında yolu bulmak ve var olanı güncellenmek için kullanılırlar. Yönlendirme protokolleri proaktif(ör. OLSR), reaktif (ör. AODV) ve karma (ör. TORA) olmak üzere sınıflara ayrılırlar. IEEE 802.11 veya WI-FI olarak da bilinen kablosuz LAN standardının 802.11a, 802.11b ve 802.11 gibi farklı varyasyonlar vardır. Bu tezde, HTTP Protokolü’nün kullandığı web uygulaması kullanılarak 802.11b ve 802.11g standartları farklı veri oranlarında karşılaştırılmıştır. Simülasyonlarda kullanılan yönlendirme protokolü Ad hoc on- demand Distance Vector (AODV) Protokolü’dür. Sistemin performansı, her yönde seçilen sekme sayısı ( number of hopsperroute), HTTP sayfa yanıt zamanı (HTTP page response time), HTTP nesne yanıt zamanı ( HTTP objectresponse time ), ortam giriş gecikmesi (media Access delay ), paketlerin yeniden gönderim girişi (retransmission attempts) (packet) ve üretilmiştir (throughput) ölçütleri kullanılarak analiz edilmiştir. OPNET simülatör versiyon 17.1 ad hoc ağlarının modellenmesi ve simülasyonu için kullanılmıştır. vi Simülasyon sonuçlarından elde edilen sonuçlar ortama giriş gecikmez sistemde olan bütün kullanım saflarında 802.11b’de 802.11g’den daha fazladır. 802.11g’de veri hızı arttırıldığı zaman yeniden gönderim girişimi azalıyor. Ağda üretilen iş arası 11Mbps veri hızında 802.11g’de 802,11b’den daha fazladır. Buna ek olarak her iki standartta da üretilen iş oranı sunucuyla iletişime geçen düğüm sayısı arttıkça artıyor. Anahtar Kelimeler: MANET, AODV, HTTP, IEEE 802.11, OPNET.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2013. Supervisor: Assist. Prof. Dr. Gürcü Öz.
Keywords: Computer Engineering; Wireless sensor networks; Wireless communication systems; Wireless LANs - Standards; MANET, AODV, HTTP, IEEE 802.11, OPNET